Wood consumption and fixations of carbon dioxide and carbon from timber housing techniques: A Brazilian panorama - De Araujo, Victor; Vasconcelos, Juliano [UNESP]; Cortez-Barbosa, Juliana [UNESP]; Morales, Elen [UNESP]; Christoforo, Andre; Gava, Maristela; Lahr, Francisco; Garcia, Jose (Elsevier B.V., 2020)
This paper evaluated lignocellulosic biomass volume, in net and gross forms, consumed by Brazilian wood-based housing producers by building technique, as well as net volumes of fixed carbon and carbon dioxide by built area. Net volumetric values of consumed wood per available technique were obtained for single-story house with 100 m(2) of built area, whose data collection was supported by face-to-face interviews with Brazilian producers. Gross volumes were obtained according to wood machining yield described in literature. Determinations of fixed carbon and carbon dioxide were verified by means of net volumes per built area, being calculated from data collected in the interviews. In wood consumption for this standard 100 m(2) house, most of construction techniques revealed average net volumes from 8 to 15 m(3) and gross volumes from 15 to 24 m(3) and from 13 to 21 m(3), respectively, for 30% and 55% yields. In net volumes for 100 m(2) house, the lowest wood consumption was 2 m(3) (or 0.02 m(3) per m(2) of built area) obtained by two versions of nailed clapboard technique, while the highest amount of wood consumed was 34 m(3) (0.34 m(3)/m(2)) for modular technique in cross-laminated timber. As regards carbon fixation, contemporary techniques mostly based on eucalypt and pine species ranged from 30 to 40 kg(C)/m(2), while this range was from 35 to 55 kg(C)/m(2) for traditional techniques largely made with natives. For native woods, the lowest carbon fixation was obtained by stick with masonry technique with parica(12 kg(C)/m(2)), and the highest value was observed in log-home technique using sapucaia (92 kg(C)/m(2)). In exotics, modular for construction site with loblolly pine presented the lowest fixation (19 kg(C)/m(2)), and the possibility of modular technique in cross-laminated timber with blue spotted gum had the highest level (107 kg(C)/m(2)). High wood consumptions were influenced by obsolete production technologies and robust techniques, evincing expressive fixations. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Carbon; Carbon dioxide; Biomass volume; Wood; Housing; Sectoral survey